What is the impact of EUR/CZK exchange rate on different labour markets in the Czech Republic? - Šimáně, Jaromír (2012)
The short-run impacts of real and nominal exchange rate between Czech Crown and Euro to Czech labour markets are investigated. 27 different labour markets are analysed, 5 of them are significantly affected by exchange rate with elasticities ranging from -0.09 to -0.50. Appreciation decrease employment in all of them. Non-linear method offered by Belke and Göcke is explained, used and compared with standard least squares. Standard labour market statistics are augmented with the job vacancies to find elasticity on number of jobs as well.